A FONOLOGIA FORNECENDO PISTAS SOBRE A SINTAXE: O CASO DOS OBJETOS NULOS - Raquel Santana Santos (Cadernos de Estudos Lingüísticos, 2011)
The aim of this paper is to offer more evidence in favor of Cyrino’s analysis (1994) of the null object in Brazilian Portuguese. This evidence comes from the analysis of clash resolution, according to the Prosodic Theory of Nespor & Vogel (1986).